Trypanosomosis in a Sambar deer - Abdullah, Faez Firdaus Jesse; Mohammed, Konto; Shahudin, Muhammad Syafiq; Adamu, Lawan; Osman, Abdinasir Yusuf; Abba, Yusuf; Tijjani, Abdulnasir; Roslim, Noorashimah; Awang, Dayang Norhaizam; Saharee, Abdul Aziz; Saad, Mohd Zamri; Haron, Abd Wahid (International Organization of Scientific Research, 2014)
A five years old Sambar deer was presented to the University Veterinary Hospital of Universiti Putra Malaysia. The deer was physically diagnosed with clinical signs of depression, lethargy, teeth grinding, pallor of mucous membranes, the vital parameters showed pyrexia (40.90C), increase in pulse (197beats/min.) and respiratory rates (42 circles/min.). Laboratory examination of the Buffy coat by micro haematocrit centrifugation technique revealed the presence of motile flagellates. Buffy coat smear examination confirmed the presence of Trypanosome spp. The disease was diagnosed based on clinical signs and laboratory finding. Diminazene Aceturate at a dose rate of 3.5mg/kg bodyweight was administered intramuscularly, coupled with multivitamin and fluid therapy proves effective in treating the condition. This report shows the significance of wild ruminants in maintaining the transmission cycle of this parasite and timely treatment could resolve the disease condition.